Non-catalytic hydrolysis of sea mango (Cerbera odollam) oil and various non-edible oils to improve their solubility in alcohol for biodiesel production - Kansedo, Jibrail; Lee, K. (Elsevier BV, 2014)
This study investigates the non-catalytic hydrolysis of various non-edible oils as an alternative way to improve their solubility in alcohol by increasing their free fatty acids content. A number of parameters were investigated and optimized; hydrolysis temperature (170-200. °C), hydrolysis time (2.5-15.0. h), volume ratio of oil to water (80:20-20:80), and hydrolysis pressure (0.1-3.0. MPa). A comparative experiment using homogenous catalyst (acetic acid) was also carried out. The extent of the hydrolysis process was measured by the acid number of the hydrolyzed oil. Volume ratio of oil to water and hydrolysis temperature were found to have the greatest effect on the hydrolysis process whereby highest hydrolysis temperature (200. °C) and largest volume ratio of oil to water (20:80) resulted to hydrolyzed products with the highest acid value. Hydrolysis pressure was found to have adverse effect on the hydrolysis process. The successful hydrolysis of various edible and non-edible oils suggested that it is possible to completely convert oils into fatty acids at low temperature without the use of catalyst, as an alternative way to improve their solubility in alcohol for biodiesel production.